Implementasi Pemerintah Provinsi Riau dalam Pemerataan Guru Agama Sekolah Menengah Atas Berdasarkan Prinsip Profesionalitas dalam Undang-Undang nomor 14 Tahun 2005 tentang Guru dan Dosen di Provinsi Riau - Sianturi, Pagar Parlindungan; Indra, Mexsasai; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The State of Indonesia is a state of law that adheres to the principle of decentralization in the administration of government, one of which is the equalization of high school religious teachers based on the Principle of Professionalism in Law Number 14 of 2005 concerning Teachers and Lecturers in government affairs in Riau Province, which at present is not in accordance with what was claimed - tell me the invitations. The research method in this study is a research method with sociological juridical research or sociological legal research. The theoretical basis used is the theory of regional governance, and law enforcement theory.The purpose of this thesis discussion, namely: to discuss the implementation of the Riau provincial government in examining high school religious teachers on the principle of professionalism in Law number 14 of 2005 concerning teachers and instructors in Riau Province, secondly to find out what is related to the Riau provincial government in equitable distribution high school religious teachers based on the principle of professionalism in law number 14 of 2005 concerning teachers and lecturers in Riau province, thirdly to find out the provincial government of Riau in overcoming the problem of examining high school religion teachers on the basis of professionalism in law number 14 of 2005 about teachers and lecturers in Riau Province.From the results of research and discussion it can be concluded that the implementation of the provincial government in the distribution of high school religion teachers based on the principle of professionalism in Law number 14 of 2005 on Teachers and Lecturers in Riau Province has not been carried out in accordance with what is envisioned by the law, religious teachers what is really needed as an educator of religious values for students is not available and not fulfilled in every region. Factors that are considered by the provincial government are internal and external factors, and to overcome this. So some efforts were made by the provincial government to examine religious teachers at the high school level, namely: conducting data collection and mapping of religious teachers in all high schools regarding the needs of religious teachers; then the provincial government submits data on the needs of religious teachers to the central government to be asked to meet the needs of further religious teachers and the provincial government conducts training of new and old religious teachers for training and socialization of semester expenditure / curriculum materials. Thus the examination of top-level religious teachers based on the principle of professionalism in law number 14 of 2005 concerning teachers and lecturers in Riau province can be realized properly.Keywords: Implementation, Equality, Religious Teachers